2021
DOI: 10.1001/jamapsychiatry.2021.0042
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Prevalence and Incidence of Dementia Diagnoses Among Older US Adults With Schizophrenia

Abstract: IMPORTANCE People with schizophrenia are at high risk of receiving a diagnosis of dementia. Understanding the magnitude and timing of this increased risk has important implications for practice and policy.OBJECTIVE To estimate the age-specific incidence and prevalence of dementia diagnoses among older US adults with schizophrenia and in a comparison group without serious mental illness (SMI). DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study used a 50% random national sample of Medicare benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 36 publications
6
61
0
2
Order By: Relevance
“…Nine studies conducted in Australia, Asia, Europe and North America reported associations between psychotic disorders and dementia (Table 1). Sample sizes ranged from 12,616 54 to 8,011,773, 22 and follow‐up periods were between 4 55 to 33 years 33 . Studies were good ( n = 8) or poor ( n = 1) quality.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies conducted in Australia, Asia, Europe and North America reported associations between psychotic disorders and dementia (Table 1). Sample sizes ranged from 12,616 54 to 8,011,773, 22 and follow‐up periods were between 4 55 to 33 years 33 . Studies were good ( n = 8) or poor ( n = 1) quality.…”
Section: Resultsmentioning
confidence: 99%
“…Dementia is one such example, recently reported to be much more prevalent among patients with schizophrenia. Dementia is also a known risk factor for pneumonia [46,47]. There are also other socioeconomic and environmental differences; individuals with SMDs are more likely to be homeless, unemployed, and live in poverty, all of which may affect access to healthcare and increase the risk of infection [48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…70 Cerebral hypoperfusion is more common in older schizophrenia patients, however, where it worsens at a greater rate than expected from normal aging. 58 If such cerebral vascular changes are found to contribute to the strikingly increased rates of early and late dementia diagnoses in people with schizophrenia, 71 OCTA could be an expedient and non-invasive method for monitoring neurovascular degeneration and cognitive decline in schizophrenia and other conditions associated with microvasculature changes, including atrophy over time.…”
Section: Dovepressmentioning
confidence: 99%